Introduction to probability with Texas hold'em examples - Schoenberg, Frederic Paik (CRC Press, 2012)
"Introduction to Probability with Texas Hold'em Examples illustrates both standard and advanced probability topics using the popular poker game of Texas Hold'em, rather than the typical balls in urns. The author uses students' natural interest in poker to teach important concepts in probability. This classroom-tested book covers the main subjects of a standard undergraduate probability course, including basic probability rules, standard models for describing collections of data, and the laws of large numbers. It also discusses several more advanced topics, such as the ballot theorem, the arcsine law, and random walks, as well as some specialized poker issues, such as the quantification of luck and skill in Texas Hold'em. Homework problems are provided at the end of each chapter. The author includes examples of actual hands of Texas Hold'em from the World Series of Poker and other major tournaments and televised games. He also explains how to use R to simulate Texas Hold'em tournaments for student projects. R functions for running the tournaments are freely available from CRAN"--Back cover.